Investigation of Band Alignment for Hybrid 2D-MoS2/3D-β-Ga2O3 Heterojunctions with Nitridation - Ya-Wei Huan; Ke Xu; Wen-Jun Liu; Hao Zhang; Dmitriy Anatolyevich Golosov; Chang-Tai Xia; Hong-Yu Yu; Xiao-Han Wu; Qing-Qing Sun; Shi-Jin Ding (Nanoscale Research Letters, 2019)
Abstract Hybrid heterojunctions based on two-dimensional (2D) and conventional three-dimensional (3D) materials provide a promising way toward nanoelectronic devices with engineered features. In this work, we investigated the band alignment of a mixed-dimensional heterojunction composed of transferred MoS2 on β-Ga2O3( 2- $$ 2- $$01) with and without nitridation. The conduction and valence band offsets for unnitrided 2D-MoS2/3D-β-Ga2O3 heterojunction were determined to be respectively 0.43 ± 0.1 and 2.87 ± 0.1 eV. For the nitrided heterojunction, the conduction and valence band offsets were deduced to 0.68 ± 0.1 and 2.62 ± 0.1 eV, respectively. The modified band alignment could result from the dipole formed by charge transfer across the heterojunction interface. The effect of nitridation on the band alignments between group III oxides and transition metal dichalcogenides will supply feasible technical routes for designing their heterojunction-based electronic and optoelectronic devices.